Β-1, 3-Glucan/chitin unmasking in the Saccharomyces cerevisiae mutant, Δmnn9, promotes immune response and resistance of the Pacific oyster (Crassostrea gigas) to Vibrio coralliilyticus infection. Issue 131 (December 2022) - Loor, Alfredo; Wang, Dongdong; Bossier, Peter; Nevejan, Nancy
Abstract: Yeast cells can play a crucial role in immune activation in fish and shellfish predominantly due to the cell wall component β-1, 3-glucan, providing protection against bacterial or viral infections. However, the immunostimulatory capacity of dietary yeast cells remains poorly studied in bivalves. To understand the role of yeast cell wall components (mannan, β-glucan and chitin) as immune activators, this study characterized the surface carbohydrate exposure of the wild-type baker's yeast Saccharomyces cerevisiae (WT) and its Δ mnn9 mutant, which presents a defective mannan structure, and compared these profiles with that of β-glucan particles, using fluorescein isothiocyanate (FITC)-labeled lectin binding analysis. Then, a first trial evaluated the immunological response in Crassostrea gigas juveniles after being fed for 24 h with an algae-based diet (100A) and its 50% substituted version (based on dry weight) with WT (50A50WT) and Δ mnn9 (50A50Y), and the posterior resistance of the juveniles against Vibrio coralliilyticus infection (trial 1). The mRNA expression was measured for β-glucan-binding protein ( Cg βGBP), Toll-like receptor 4 ( Cg TLR4), C-type lectin receptor 3 ( Cg CLec-3), myeloid differentiation factor 88 ( Cg MyD88), nuclear factor-kappa B ( Cg NFκB), lysozyme ( Cg Lys), interleukin 17-5 ( Cg IL17-5), and superoxide dismutase ( Cg SOD), in oysters, before and 24 h after the bacterial inoculation. A second trial tested the effect of incorporating Δ mnn9 into the 100A diet for 24 h at different substitution levels: 0, 5, 10, 25, and 50% (100A, 95A5Y, 90A10Y, 75A25Y, and 50A50Y), followed by the bacterial challenge with V. coralliilyticus (trial 2). Our findings showed that the outer cell wall surface of WT is largely composed of mannan, while Δ mnn9 presents high exposure of β-glucan and chitin, exhibiting similar FITC-lectin binding profiles (fluorescence intensity) to β-glucan particles. A significantly higher survival after the bacterial challenge was observed in oysters fed on 50A50Y compared to those fed 50A50WT and 100A in trial 1. This better performance of 50A50Y was supported by significantly higher gene expressions of Cg Lys, Cg SOD, Cg MyD88, and Cg βGBP compared to 100A, and Cg SOD and Cg NFκB in relation to those fed on 50A50WT, prior to the bacterial inoculation. Furthermore, improved survival was observed in oysters fed 50A50Y compared to those offered lower Δ mnn9 levels and 100A in trial 2. The superior performance of Δ mnn9 -fed oysters is mostly associated with the elevated presence of unmasked β-glucans on Δ mnn9 cell wall surface, facilitating their interactions with oyster hemocytes. Further studies are needed to evaluate administration dose and frequency of Δ mnn9 to develop strategies for long-term feeding. Highlights: Outermost layer of Saccharomyces cerevisiae Δ mnn9 has elevated β-glucan and chitin exposure. Δ mnn9 cells support Lysozyme, SOD, MyD88, and β-GBP expressions in Crassostrea gigas . Immune response is associated with higher β-glucan-hemocyte interaction in the digestive tract. Δ mnn9 -fed C. gigas exhibited higher resistance against Vibrio coralliilyticus infection. Δ mnn9 supplied at 50% of diet promotes higher survival in oysters than those fed lower levels.